2002
DOI: 10.1542/peds.110.4.e42
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Neonates With Suspected Late-Onset Sepsis: A Survey of Neonatologists’ Practices

Abstract: ABSTRACT.Objective. To ascertain current diagnostic and treatment practices for suspected late-onset sepsis in infants in neonatal intensive care units (NICUs) and identify areas that may benefit from clinical practice guidelines.Methods. During June 2000, we conducted a multicenter survey of neonatologists and infection control professionals regarding practices related to late-onset sepsis in NICUs at children's hospitals participating in the Pediatric Prevention Network.Results. Personnel at 35 hospitals wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0
9

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(128 citation statements)
references
References 25 publications
2
117
0
9
Order By: Relevance
“…Developing a prediction score without including these neonates will result in poor performance of prediction score in subsequent validation studies and was clearly evidenced by Mahieu et al 3 Acute phase protein measurement (such as C-reactive protein, and other cytokines) was commonly used for diagnosis of LNS in many neonatal care settings; however, the utility of such tests in decision-making is limited by test performance, availability, and turn-around time. 19,20 Our prediction score does show significant overlapping with other prediction scores especially the NOSEP score. 3 Although our results overlapped with this study, we had derived the score using larger sample size and also including more general infants.…”
Section: Discussionmentioning
confidence: 64%
“…Developing a prediction score without including these neonates will result in poor performance of prediction score in subsequent validation studies and was clearly evidenced by Mahieu et al 3 Acute phase protein measurement (such as C-reactive protein, and other cytokines) was commonly used for diagnosis of LNS in many neonatal care settings; however, the utility of such tests in decision-making is limited by test performance, availability, and turn-around time. 19,20 Our prediction score does show significant overlapping with other prediction scores especially the NOSEP score. 3 Although our results overlapped with this study, we had derived the score using larger sample size and also including more general infants.…”
Section: Discussionmentioning
confidence: 64%
“…CONS is a common blood culture isolate when blood cultures are performed during evaluation for late-onset sepsis in NICUs. The majority of neonatologists who were polled by Rubin et al 16 reported their preference for use of vancomycin as a first-line agent for suspected late-onset sepsis in certain clinical scenarios. This contradicts the findings by multiple authors 17,18 that the mortality as a result of CONS late-onset sepsis is no different when using vancomycin empirically versus using vancomycin in a restricted protocol.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, coagulase-negative staphylococci were usually believed to represent contamination when isolated from blood cultures. In fact, coagulase-negative staphylococci are the most common blood culture contaminants, typically representing 70% to 80% of all contaminated blood cultures (25,92,105,113,125).…”
Section: Identity Of Organismmentioning
confidence: 99%
“…Recently, however, studies have shown that these organisms are an increasing source of true bacteremia in patients with prosthetic devices and central venous catheters (30,53,105,139,155), although the majority of isolates of coagulase-negative staphylococci from blood cultures continue to be contaminants. Weinstein et al found that even though only 12.4% of coagulase-negative staphylococcal isolates were clinically significant, they ranked as the third most common cause of bacteremia because of their high prevalence (155).…”
Section: Identity Of Organismmentioning
confidence: 99%